Analysis of Lake Beseka Water Using Inductivity Coupled Plasma Optical Emission Spectrometry (ICP-OES) Technique - Assefa Eba (ASTU, 2016)
This study focuses on the analysis of Lake Beseka water to check whether it is potable and also could be used for irrigation. Thus health risk factors if it is consumed by human population and wild and household animals and plants living around the river are studied. Samples of water were taken from five surface sampling points distributed around Beseka Lake and from five sampling points on Awash River starting from the entrance point of the discharging water from Beseka Lake in to the river. The parameter studied were EC, pH, TDS, Fe-, F-, Al+3, Cr -, Cn, SO4-2, NO3 and NH4+.The values of the parameters were compared with respect to the maximum accept able standard level (guide line value) of WHO (World Health Organization) for drinking water. The instrument used to determine the parameters were ICP-OES, PH meter, and conductometer. The outcome of this study reveals that the chemical and the physical properties of the lake is out of the WHO standards to be use both for drinking and irrigation purposes. As a result, the physical and chemical composition of the Awash River was found affected by the introduction of the water of Lake Bseka by letting it with drainage canal into the river. Finally, this study recommends possible options of solutions which minimizes the aggravation of the expansion of the lake and indicate preferable instrument of water quality monitoring process.